Studies on the text and versions of the Hebrew Bible in honour of Robert Gordon - Gordon, R. P.; Khan, Geoffrey.; Lipton, Diana. (Vetus Testamentum, Supplements, 2012)
This collection of previously unpublished essays by outstanding international scholars in honour of Robert P. Gordon, Regius Professor of Hebrew at Cambridge University, covers a wide range of topics, from accuracy, anachronism, and incongruity in the books of Samuel, through the theology of Psalms, ancient Near eastern historiography, and the ideology of the Septuagint, to philology and grammar in the Dead Sea Scrolls, Targum, Josephus, and medieval sources. It should interest readers concerned with inner-biblical exegesis and the Hebrew Bible in relation to its parallels, translations, and versions, as well as with big questions about the classification of the Bible and its antecedents as books, the social context of the Dead Sea Scrolls, and Christian attitudes towards 'original Hebrew'.